Managing soil organic matter through biochar application and varying levels of N fertilisation increases the rate of water-stable aggregates formation - Šimanský Vladimír; Wójcik-Gront Elżbieta; Buchkina Natalya; Horák Ján (Journal of Hydrology and Hydromechanics, 2023)
The formation of soil aggregates, including water-stable aggregates, is linked to soil organic matter (SOM). Biochar (B) is carbon-rich, which, in addition to storing carbon in a stable form for many years, has important benefits for soils and plants, but the mechanisms of soil structure formation after B and mineral fertiliser application are not sufficiently studied. For this reason, the study aimed to answer the following questions: How (1) the rate of B and (2) varying levels of nitrogen fertiliser (N) being applied to the soil affect the dynamics of soil aggregation due to the increase in the content of soil organic carbon, labile carbon in the bulk soil and in the content of water-stable aggregates (WSA) size-fractions. In 2014–2021, in Dolná Malanta (experimental site of Slovak University of Agriculture on silty loam Haplic Luvisol) during the growing seasons, soil samples were collected from all the B (0, 10 and 20 t ha–1) and N (0, 1st and 2nd level of N fertilisation) treatments. The results have shown that the highest values of many variables were associated with B20 treatment for all the N fertilisation levels. B compared to N more significantly affected the content of almost all the size-fractions of WSA. In all the treatments, the content of WSAma >5 mm, 5–3 mm, 3–2 mm and 1–0.5 mm in size was increasing over time – a yearly increase from 0.31 to 2.14% for 8-years. Based on the changes in the SOM content, WSA were divided into 3 groups: 1) Water-stable microaggregates (WSAmi < 0.25 mm), 2) Smaller size-fractions of water-stable macroaggregates (WSAma 1–0.25 mm), and 3) Medium and large fractions of WSAma (WSAma ≥1 mm).